2017
DOI: 10.3389/fpsyt.2017.00030
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Resting-State Functional Connectivity in Current and Recovered Restrictive Anorexia Nervosa

Abstract: Functional connectivity studies based on resting-state functional magnetic resonance imaging (rs-fMRI) have shown alterations in brain networks associated with self-referential processing, cognitive control, and somatosensory processing in anorexia nervosa (AN). This study aimed to further investigate the functional connectivity of resting-state networks (RSNs) in homogenous subsamples of individuals with restrictive AN (current and recovered) and the relationship this has with core eating disorder psychopatho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
31
4
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 83 publications
(91 reference statements)
11
31
4
2
Order By: Relevance
“…As frontal activation has been shown to change with psychotropics (Posner et al, ), medication status may influence frontostriatal circuit connectivity results. However, while the discrepancy in our results is likely due in part to these methodological differences, the divergence in our findings also mirrors results from the broader fMRI literature in AN in which some studies have found evidence of increased neural activity within the frontostriatal system (Cowdrey, Park, Harmer, & McCabe, ; Frank et al, ) while others have found the opposite (Brooks et al, ; Scaife et al, ; Wagner et al, ). Moving forward, it will be important to discern whether the heterogeneity in results stems from variability in methodology or reflects an underlying complexity of frontostriatal circuitry in AN.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…As frontal activation has been shown to change with psychotropics (Posner et al, ), medication status may influence frontostriatal circuit connectivity results. However, while the discrepancy in our results is likely due in part to these methodological differences, the divergence in our findings also mirrors results from the broader fMRI literature in AN in which some studies have found evidence of increased neural activity within the frontostriatal system (Cowdrey, Park, Harmer, & McCabe, ; Frank et al, ) while others have found the opposite (Brooks et al, ; Scaife et al, ; Wagner et al, ). Moving forward, it will be important to discern whether the heterogeneity in results stems from variability in methodology or reflects an underlying complexity of frontostriatal circuitry in AN.…”
Section: Discussionsupporting
confidence: 63%
“…Gaudio et al () identified decreased connectivity in the ECN in adolescents with new‐onset illness, while others have found abnormal connectivity within the Frontoparietal Network (FPN; analogous to the ECN) in ill and recovered participants with AN (Boehm et al, ). On the other hand, several studies have not found significant differences in the networks implicated in the triple network model in underweight individuals with AN (Boehm et al, ; Scaife, Godier, Filippini, Harmer, & Park, ) or participants recovered from AN relative to HC (Boehm et al, ; Phillipou et al, ; Scaife et al, ). One study that used FNC to measure cross‐network connectivity of these systems found no difference in network interactions between the SN, DMN, and FPN among women recovered from AN and HC (Boehm et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Greater cortical thinning could, in turn, increase vulnerability to AN by disrupting communication between and/or within networks subserving perception of and/or attention to body shape and size. Altered resting-state functional connectivity, consistent with this hypothesis, has been reported in AN;Phillipou et al (2016) reported reduced resting-state functional connectivity between visual association and sensorimotor areas in women with acute AN, andFavaro et al (2012) andScaife, Godier, Filippini, Harmer & Park (2017) reported reduced resting-state functional connectivity within ventral and lateral visual networks, respectively, in women with acute and remitted AN.…”
supporting
confidence: 76%
“…Additionally, the findings of the correlation analyses may be limited by a relatively small sample size and multiple comparisons and, thus, need to be replicated. There is also evidence that structural differences between AN and HC groups could impact patterns of RSFC (Scaife, Godier, Filippini, Harmer, & Park, 2017). For this reason, it is possible that the findings of this study could be accounted for by the documented differences in the structure of frontostriatal regions between and AN and HC groups (Frank, Shott, Riederer, & Pryor, 2016; Frank et al, 2013; Zhang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%